2009
DOI: 10.1051/0004-6361/200912009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clustering analysis of variable stars in the Hipparcos, OGLE Large Magellanic Cloud, and CoRoT exoplanet databases

Abstract: Context. Discovery of new variability classes in large surveys using multivariate statistics techniques such as clustering, relies heavily on the correct understanding of the distribution of known classes as point processes in parameter space. Aims. Our objective is to analyze the correspondence between the classical stellar variability types and the clusters found in the distribution of light curve parameters and colour indices of stars in the CoRoT exoplanet sample. The final aim is to help in the identifica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…What we can observe is that whereas for low frequencies it is not trivial for any clear relation to be detected, the high-frequency domain is dominated by eclipsing binaries of all three classes with 21 ≈ 0. This is in accordance with the results from the analysis of the Hipparcos archive presented in [10].…”
Section: Epj Web Of Conferencessupporting
confidence: 92%
See 1 more Smart Citation
“…What we can observe is that whereas for low frequencies it is not trivial for any clear relation to be detected, the high-frequency domain is dominated by eclipsing binaries of all three classes with 21 ≈ 0. This is in accordance with the results from the analysis of the Hipparcos archive presented in [10].…”
Section: Epj Web Of Conferencessupporting
confidence: 92%
“…Hot Planets and Cool Stars Previous studies [9,10] have demonstrated that various parameters resulting from the analysis of the light curves can be used to successfully classify the objects in one class or another. For example, optical data from Hipparcos, OGLE and CoRoT have been used for the determination of robust sets of parameters derived from the light curves of known member stars of various variability classes.…”
Section: -P4mentioning
confidence: 99%
“…Recent development of modern machine learning techniques and high performance computing architectures have made possible the efficient execution of automated probabilistic multi-class classification of very large datasets in reasonable time frames (Debosscher et al, 2007;Sarro et al, 2009aSarro et al, , 2009bDebosscher et al, 2009;Richards et al, 2011Richards et al, , 2012Blomme et al, 2011;Matijevič et al, 2012;Morgan et al, 2012;Long et al, 2012). An essential step in the development of such a framework is processing a large set of events of known class to train the classifier.…”
Section: Discussionmentioning
confidence: 99%
“…We keep improving the capabilities of the classifiers, and have now extended our training set to be able to recognize light curves showing the signs of rotational modulation and activity. We used the clustering results obtained from the CoRoT data, as presented in Sarro et al (2009), to define these two new classes. Their template data consist of CoRoT exoplanet field light curves for now, but they will be extended in the future, since Kepler will provide many new examples.…”
Section: Methodsmentioning
confidence: 99%